The Influence Of Work Environment and Leadership Style On Employees Performance At Supporting Division PT. XYZ Which Is Moderated by Work Motivation - Prabowo, Pancanto Kuat; Utama, Johan Surya (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2024)
An organization, be it a company, institution or community, requires competent and skilled human resources so that the operational system within it can run well. The purpose of this study is to examine the influence of work environment and leadership style on employee performance which is moderated by work motivation as an intervening variable. This research uses quantitative methods whose samples are taken from the supporting division, one of the divisions at PT. XYZ. The sampling technique uses probability sampling in the form simple random random where the sample used is all employees in the supporting division, amount 41 people. The analytical method used in this research is moderated regression analysis assisted by the SPSS application.